MONITORAMENTO DE SUBSIDÊNCIA DO TERRENO DEVIDO A EXPLORAÇÃO DE AQUÍFERO CARSTICO - Nadal, Carlos Aurélio; Ratton, Eduardo; Rosa Filho, Ernani Francisco da; Giusti, Donizeti Antonio; Bittencourt, André Virmond de Lima; Juliano, Katia Aparecida (Águas Subterrâneas, 1995)
Resumo não disponivel.